Catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of catalyst
By loading ruthenium on the SOD molecular sieve, a ruthenium-based hydrogen production catalyst is formed, which solves the problems of high operating temperature and high cost of existing catalysts, and achieves the effect of efficient preparation of hydrogen at lower temperatures.
Patent Information
- Application Number
- CN202411669235.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The high operating temperature and high cost of existing ammonia decomposition hydrogen production catalysts limit their large-scale commercial applications.
By preparing SOD molecular sieve and supporting ruthenium thereon, a ruthenium-based hydrogen production catalyst is formed, which reduces the operating temperature of the catalyst and improves its stability.
A high conversion rate of ammonia hydrogen production effect is achieved at a lower temperature (500°C), reducing production costs and avoiding the problem of easy deactivation of ruthenium-based catalysts.
Smart Images

Figure CN119680630A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ammonia decomposition hydrogen production catalysts, and in particular to an ammonia decomposition hydrogen production catalyst and a preparation method and application thereof. Background Art
[0002] When traditional fossil fuels are burned, processed chemically, etc., they will inevitably release a large amount of carbon dioxide, causing environmental problems. Under the global demand for carbon reduction, the development and utilization of non-carbon new energy is of great significance. Hydrogen (H) energy is regarded as an ultimate clean fuel because of its high energy density (120 MJ / kg) and the fact that it only produces water and does not emit carbon dioxide when burned. However, hydrogen has a wide range of flammability and low ignition energy (0.17 kJ / mol), which makes it face huge risks during transportation and storage. Due to the lack of effective storage and transportation (storing H2 in cylinders requires a high pressure of about 700 bar), the direct use of hydrogen has been greatly hindered. Therefore, the development of a "hydrogen carrier" that is low-cost, high-density, high-storage-efficiency, and can be decomposed on demand to produce hydrogen is regarded as the key to solving the problem of effective utilization of hydrogen energy.
[0003] Ammonia (NH3) contains 17.8wt% H, and can produce nitrogen (N2) and hydrogen (H2) in a volume ratio of 1:3 by decomposition. Compared with carbon-based hydrogen carriers (such as methanol, methane, etc.) that produce carbon dioxide during hydrogen production, ammonia has attracted widespread attention for its high hydrogen yield and zero carbon emissions (Valera-Medina, A. et al, Energy. Fuels. 2021, 35, 6964). Ammonia decomposition to produce hydrogen provides new possibilities for the low-carbon transformation of the hydrogen energy economy (Goetsch, DA et al, WO Patent, 2001, 0187770). For more than 20 years, the development of efficient catalysts has been the key to ammonia decomposition to produce hydrogen technology. Ruthenium-based catalysts and ruthenium-based catalysts are currently the main research areas (Schuth, R. et al, Energy. Environ. Sci, 2012, 5, 6278). Ruthenium catalysts have high ammonia decomposition activity and can decompose ammonia at 350-500°C (CN107876796B; Nagaoka, K. et al, Sci Advs, 2017, 3, e1602747), but the scarcity and high cost of Ru limit its large-scale commercial application. Therefore, the preparation of Ru catalysts with low production cost, low operating temperature, high conversion rate and long life is the key to realize the large-scale commercial application of ammonia catalytic decomposition to produce hydrogen. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an ammonia decomposition hydrogen production catalyst and its preparation method and application. First, a SOD molecular sieve is prepared, and then ruthenium is loaded onto the SOD molecular sieve to obtain a ruthenium-based ammonia decomposition hydrogen production catalyst. The catalyst has high stability and can be used sustainably, and the temperature of ammonia decomposition hydrogen production is reduced, thereby reducing costs, effectively avoiding the problems of high operating temperature and high cost of ruthenium-based catalysts.
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a catalyst for hydrogen production by decomposing ammonia, comprising the following steps:
[0006] S1, mixing aluminum source, silicon source, sodium hydroxide and water to prepare gel, and obtaining SOD molecular sieve after high temperature crystallization;
[0007] S2, mixing the SOD molecular sieve with a ruthenium salt, subjecting the mixture to high temperature heat treatment and forming to obtain a ruthenium-loaded SOD molecular sieve;
[0008] Wherein, the mass fraction of ruthenium in the ruthenium-loaded SOD molecular sieve is 0.5%-20%.
[0009] The present invention prepares SOD molecular sieve by reacting aluminum source, silicon source and sodium hydroxide. The molecular sieve has a high specific surface area, can stabilize metal nanoparticles on the surface, and regulates surface chemistry by increasing the active site density to promote the diffusion of intermediates in the reaction process. At the same time, in this reaction, increasing the basicity of the catalyst can promote the dissociation of nitrogen-hydrogen bonds, thereby improving the catalytic activity. The SOD molecular sieve stands out among many molecular sieves with its lower silicon-aluminum ratio and its own high basicity. When the SOD molecular sieve is synthesized, a large amount of sodium ions are contained in the cage. At the same time, the diameter of the SOD cage is only 0.3 nanometers, which can well fix the sodium ions. After the SOD molecular sieve is loaded with ruthenium, the sodium ions can provide electrons to the metal ruthenium, accelerate the activation of the metal ruthenium, and further reduce the temperature at which ammonia is completely decomposed. Experiments have shown that the molecular sieve with high alkali metal concentration is more reactive than the catalyst without adding alkali metal.
[0010] Therefore, the Ru-SOD catalyst can obtain a good conversion rate at a relatively low temperature (500°C). Through the above means, the problem of high operating temperature and easy deactivation of ruthenium-based catalysts is effectively avoided. In addition, the preparation method is simple and can be mass-produced.
[0011] Furthermore, in S2, the mixing method is one of coprecipitation, ball milling, and impregnation.
[0012] Furthermore, the co-precipitation is specifically as follows: mixing the SOD molecular sieve with a ruthenium salt aqueous solution with a mass concentration of 0.5 mol / L-2 mol / L, stirring at a pH of 8.5-9.5, filtering, washing and drying after precipitation.
[0013] Furthermore, the impregnation specifically includes: mixing the SOD molecular sieve, ruthenium salt and deionized water and then drying.
[0014] Further, when the mixing method is coprecipitation or impregnation, the high temperature heat treatment is calcination at 300-600°C and reduction in hydrogen atmosphere at 500-600°C; when the mixing method is ball milling, the high temperature heat treatment is reduction in hydrogen atmosphere at 500-600°C. Preferably, the calcination at 300-600°C is calcination at 300°C for 1h and calcination at 600°C for 3h; the reduction in hydrogen atmosphere at 500-600°C is preferably reduction at 550°C for 2h.
[0015] Furthermore, in S2, the ruthenium salt is one or more of ruthenium nitrate hexahydrate, ruthenium carbonate, and ruthenium chloride.
[0016] Furthermore, in S1, the aluminum source is one or more of sodium aluminate, aluminum hydroxide, and aluminum isopropoxide.
[0017] Furthermore, in S1, the silicon source is one or more of sodium silicate nonahydrate, silica gel, and fumed silica.
[0018] Furthermore, in S1, the molar ratio of sodium, aluminum and silicon in the SOD molecular sieve is 7.5:1:(1-4).
[0019] Furthermore, in S1, the temperature of high temperature crystallization is 80-120° C. and the pressure is normal pressure.
[0020] Furthermore, the forming is tableting followed by screening.
[0021] The second aspect of the present invention provides a catalyst for hydrogen production by decomposing ammonia prepared by the preparation method described in the first aspect.
[0022] The third aspect of the present invention provides the use of the catalyst described in the geothermal aspect, wherein the catalyst is loaded in a fixed bed reactor, and ammonia passes through the catalyst bed to undergo a decomposition reaction at 200-600°C.
[0023] Furthermore, the mass space velocity of the decomposition reaction is 600-60000 mL·h -1 ·g -1 .
[0024] Beneficial effects of the present invention:
[0025] The preparation method of the ruthenium catalyst for hydrogen production by decomposing ammonia is simple, which greatly reduces the difficulty of preparing the catalyst. At the same time, the catalyst has a lower operating temperature, which avoids the problem of the ruthenium-based catalyst in the prior art having an overly high operating temperature and being easily deactivated.
[0026] The SOD molecular sieve used in the present invention has a six-membered ring window with a diameter of about It can protect alkali metal ions to the greatest extent and prevent their loss. Because the SOD cage contains a large number of sodium ions, the sodium ions can provide a large number of electrons to the metal ruthenium position, which accelerates the activation of the metal ruthenium and further reduces the temperature for the complete decomposition of ammonia. By using SOD molecular sieve to load ruthenium, in the ammonia decomposition reaction system, it promotes the effective breaking of the nitrogen-hydrogen bond in the ammonia molecule, accelerates the forward progress of the equilibrium reaction, and can obtain a better conversion rate at a lower temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a comparison diagram of X-ray diffraction spectra of SOD and Ru / SOD catalyst of the present invention;
[0028] Figure 2 It is a comparison diagram of the X-ray diffraction spectra of the catalyst of the present invention before and after the ammonolysis reaction. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0030] Example 1
[0031] 44.16g ultrapure water, 2.731g sodium aluminate, 6.309g sodium hydroxide, and 9.474g sodium silicate nonahydrate were mixed and stirred to obtain a gel, the components and molar ratio of the gel were 7.5 (Na2O): 1.0 (A12O3): 2.0 (SiO2): 165 (H2O). Then, crystallization was carried out at 100°C for 12h, and the precipitate was centrifuged, washed, and dried to obtain a SOD molecular sieve.
[0032] According to the mass percentage of ruthenium ions in the molecular sieve catalyst of 1%, ruthenium chloride is added to deionized water to form a 1 mol / L ruthenium chloride solution (metal precursor solution A); sodium hydroxide is added to deionized water to form a 0.2 mol / L solution. The SOD molecular sieve is mixed with solution A, placed in a stirrer, stirred at a speed of 600r / min, and 0.2 mol / L NaOH solution is added dropwise to the mixture, and the pH value of the solution in the beaker is adjusted to 9. Stirring and aging are continued for 2 hours. After filtering and washing, it is placed in an oven for drying, calcined at 600°C for 3 hours, reduced at 550°C in a reduction furnace under a hydrogen atmosphere for 2 hours, pressed into tablets and sieved, and a 7% Ru-SOD-DP-Na catalyst is obtained by a two-step precipitation method.
[0033] The catalyst was loaded into a fixed bed reactor and the fixed bed reactor was used to evaluate the catalytic reaction of ammonia decomposition. The specific conditions were as follows: 0.5 g 1% Ru-SOD-DP-Na catalyst (40-60 mesh), reaction temperature of 200-500°C, reaction pressure of normal pressure, reaction gas ammonia flow rate of 50 ml / min, mass space velocity of 6000 mL·h -1 ·g -1 The 1% Ru-SOD-DP-Na catalyst was heated to 200°C in an inert gas atmosphere, and ammonia was introduced to react. The temperature was raised by 50°C to 500°C every 1 h to terminate the reaction, and the conversion rate of ammonia at different temperatures was detected.
[0034] Example 2
[0035] 44.16g ultrapure water, 2.731g sodium aluminate, 6.309g sodium hydroxide, and 9.474g sodium silicate nonahydrate were mixed and stirred to obtain a gel, and the components and molar ratios in the gel were 7.5 (Na2O): 1.0 (A12O3): 2.0 (SiO2): 165 (H2O). Then, crystallization was performed at 100°C for 12h to obtain a mixture of SOD molecular sieve and alkaline solution, and the pH was adjusted to 9 to obtain solution A.
[0036] According to the mass percentage of ruthenium ions in the molecular sieve catalyst being 1%, ruthenium chloride is added to deionized water to form a 1 mol / L ruthenium chloride solution (metal precursor solution B); solution B is added to solution A with a pH of 9, stirred at a speed of 600 r / min, aged for 2 hours, filtered and washed, placed in an oven for drying, calcined at 600°C for 3 hours, reduced at 550°C for 2 hours in a reduction furnace under a hydrogen atmosphere, pressed into tablets and sieved, and a 1% Ru-SOD-ODP catalyst was obtained by a one-step precipitation method.
[0037] The catalyst was loaded into a fixed bed reactor and the fixed bed reactor was used to evaluate the catalytic reaction of ammonia decomposition. The specific conditions were as follows: 0.5 g 1% Ru-SOD-ODP catalyst (40-60 mesh), reaction temperature 200-500°C, reaction pressure normal pressure, reaction gas ammonia flow rate 50 ml / min, mass space velocity 6000 mL·h -1 ·g -1 The 1% Ru-SOD-ODP catalyst was heated to 200°C in an inert gas atmosphere, and ammonia was introduced to react. The temperature was raised by 50°C to 500°C every 1 h to terminate the reaction, and the conversion rate of ammonia at different temperatures was detected.
[0038] Example 3
[0039] 44.16g ultrapure water, 2.731g sodium aluminate, 6.309g sodium hydroxide, and 9.474g sodium silicate nonahydrate were mixed and stirred to obtain a gel, wherein the components and molar ratios in the gel were 7.5 (Na2O): 1.0 (A12O3): 2.0 (SiO2): 165 (H2O). The gel was then crystallized at 100°C for 12h, and the precipitate was centrifuged, washed, and dried to obtain a SOD molecular sieve.
[0040] According to the mass percentage of ruthenium ions in the molecular sieve catalyst of 1%, ruthenium chloride was added to deionized water to form a 1 mol / L ruthenium chloride solution (metal precursor solution A); the SOD molecular sieve was mixed with solution A, placed in a stirrer, stirred at a speed of 600r / min, and 0.2 mol / L ammonia solution was added dropwise to the mixture, and the pH value of the solution in the beaker was adjusted to 9. Stirring and aging for 2 hours, after filtering and washing, it was placed in an oven for drying, calcined at 600°C for 3 hours, reduced at 550°C in a reduction furnace under a hydrogen atmosphere for 2 hours, pressed into tablets and sieved, and a 1% Ru-SOD-DP catalyst was obtained by a two-step precipitation method.
[0041] The catalyst was loaded into a fixed bed reactor and the fixed bed reactor was used to evaluate the catalytic reaction of ammonia decomposition. The specific conditions were as follows: 0.5 g 1% Ru-SOD-DP catalyst (40-60 mesh), reaction temperature of 200-500°C, reaction pressure of normal pressure, reaction gas ammonia flow rate of 50 ml / min, mass space velocity of 6000 mL·h -1 ·g -1 The 7% Ru-SOD-DP catalyst was heated to 200°C in an inert gas atmosphere, and ammonia was introduced for reaction. The temperature was raised by 50°C to 500°C every 1 h to terminate the reaction, and the conversion rate of ammonia at different temperatures was detected.
[0042] Example 4
[0043] 44.16g ultrapure water, 2.731g sodium aluminate, 6.309g sodium hydroxide, and 9.474g sodium silicate nonahydrate were mixed and stirred to obtain a gel, wherein the components and molar ratios in the gel were 7.5 (Na2O): 1.0 (A12O3): 2.0 (SiO2): 165 (H2O). The gel was then crystallized at 100°C for 12h, and the precipitate was centrifuged, washed, and dried to obtain a SOD molecular sieve.
[0044] According to the mass percentage of ruthenium ions in the molecular sieve catalyst being 1%, 0.21 g of ruthenium nitrate hexahydrate and 1.5 g of SOD molecular sieve were put into a ball mill and ball-milled for 1 hour to obtain a uniformly mixed powder, which was placed in a reduction furnace at 550°C for 2 hours under a hydrogen atmosphere, pressed into tablets and sieved to obtain a 1% Ru-SOD-QM catalyst by ball milling.
[0045] The catalyst was loaded into a fixed bed reactor and the fixed bed reactor was used to evaluate the catalytic reaction of ammonia decomposition. The specific conditions were as follows: 0.5 g 1% Ru-SOD-QM catalyst (40-60 mesh), reaction temperature of 200-500°C, reaction pressure of normal pressure, reaction gas ammonia flow rate of 50 ml / min, mass space velocity of 6000 mL·h -1 ·g -1 The 1% Ru-SOD-QM catalyst was heated to 200°C in an inert gas atmosphere, and ammonia was introduced for reaction. The temperature was raised by 50°C to 500°C every 1 h to terminate the reaction, and the conversion rate of ammonia at different temperatures was detected.
[0046] Example 5
[0047] 44.16g ultrapure water, 2.731g sodium aluminate, 6.309g sodium hydroxide, and 9.474g sodium silicate nonahydrate were mixed and stirred to obtain a gel, wherein the components and molar ratios in the gel were 7.5 (Na2O): 1.0 (A12O3): 2.0 (SiO2): 165 (H2O). The gel was then crystallized at 100°C for 12h, and the precipitate was centrifuged, washed, and dried to obtain a SOD molecular sieve.
[0048] According to the mass percentage of ruthenium ions in the molecular sieve catalyst being 1%, 0.21 g of ruthenium nitrate hexahydrate was added into 0.56 g of deionized water to dissolve to obtain solution A, solution A was dropped into 1.5 g of SOD molecular sieve and stirred continuously, dried at 80°C for 10 h, calcined at 600°C for 3 h, reduced at 550°C for 2 h in a reduction furnace under a hydrogen atmosphere, pressed into tablets and sieved, and a 1% Ru-SOD-IMP catalyst was obtained by an impregnation method.
[0049] The catalyst was loaded into a fixed bed reactor and the fixed bed reactor was used to evaluate the catalytic reaction of ammonia decomposition. The specific conditions were as follows: 0.5 g 1% Ru-SOD-IMP catalyst (40-60 mesh), reaction temperature 200-500°C, reaction pressure normal pressure, reaction gas ammonia flow rate 50 ml / min, mass space velocity 6000 mL·h -1 ·g -1 The 1% Ru-SOD-IMP catalyst was heated to 200°C in an inert gas atmosphere, and ammonia was introduced for reaction. The temperature was raised by 50°C to 500°C every hour to terminate the reaction, and the conversion rate of ammonia at different temperatures was detected.
[0050] Embodiment 6-9
[0051] The difference from Example 1 is that the mass percentage of ruthenium ions in the molecular sieve catalyst is different, and the other steps remain unchanged.
[0052] Examples 10-12
[0053] The difference from Example 3 is that the mass space velocity is different, and the other steps remain unchanged.
[0054] Examples 13-16
[0055] The difference from Example 2 is that the mass percentage of ruthenium ions in the molecular sieve catalyst is different, and the other steps remain unchanged.
[0056] The SOD molecular sieve in Example 7 and the SOD molecular sieve catalyst loaded with 1% Ru were subjected to X-ray analysis. Figure 1 As shown in FIG. 1 , after loading metal Ru, the diffraction peak position of SOD did not change, and no diffraction peak of metal oxide appeared, indicating that the preparation method of the present invention loading Ru would not destroy the structural characteristics of the carrier itself. The catalysts before and after ammonia decomposition to produce hydrogen were analyzed by X-ray. Figure 2 The diffraction peaks of the catalyst did not change before and after the catalytic reaction, indicating that the skeleton of the molecular sieve would not change during the entire catalytic process, maintaining its original shape and having good stability.
[0057] Comparative Example 1
[0058] The difference from Example 1 is that 49.5 g of ultrapure water, 4.0985 g of sodium aluminate, 0.3474 g of sodium hydroxide, and 14.21 g of sodium silicate nonahydrate are mixed and stirred to obtain a gel, and the components and molar ratios in the gel are 3.165 (Na2O): 1.0 (A12O3): 2.0 (SiO2): 160 (H2O). Subsequently, crystallization is carried out at 100° C. for 4 h, and the precipitate is centrifuged, washed, and dried to obtain a 4A molecular sieve.
[0059] The other steps remained unchanged to prepare a 1% Ru-A-DP-Na catalyst, and the conversion rate was tested using the same steps.
[0060] Comparative Example 2
[0061] The difference from Example 1 is that 45g of ultrapure water, 3.2788g of sodium aluminate, 4.2105g of sodium hydroxide, and 11.368g of sodium silicate nonahydrate are mixed and stirred to obtain a gel, and the components and molar ratios in the gel are 5.5 (Na2O): 1.0 (A12O3): 1.65 (K2O): 2.0 (SiO2): 143 (H2O). Then, the mixture is allowed to stand at 70°C for 6h, crystallized at 95°C for 3h, and the precipitate is centrifuged, washed, and dried to obtain a 13X molecular sieve.
[0062] The other steps remained unchanged to prepare a 1% Ru-X-DP-Na catalyst, and the conversion rate was tested using the same steps.
[0063] Comparative Example 3
[0064] The difference from Example 1 is that 25.4g ultrapure water, 0.18g sodium aluminate, 0.072g sodium hydroxide, 21.26g tetraethyl silicate, and 12.2g tetrapropylammonium hydroxide (TPAOH) are mixed and stirred to obtain a gel, and the components and molar ratios in the gel are 100 (SiO2): 1.1 (A12O3): 2 (Na2O): 1.0 (TPAOH): 1920 (H2O). Subsequently, crystallization is carried out at 170°C for 36h, and the precipitate is centrifuged, washed, and dried to obtain a ZSM-5 molecular sieve.
[0065] The other steps remained unchanged to prepare a 1% Ru-ZSM-5-DP-Na catalyst, and the conversion rate was tested using the same steps.
[0066] Comparative Example 4
[0067] The difference from Example 1 is that 26.9 g ultrapure water, 0.91 g sodium aluminate, 0.8 g sodium hydroxide, 39.05 g silica gel, and 2.72 g piperidine (PI) are mixed and stirred to obtain a gel, and the components and molar ratios in the gel are 20 (SiO2): 0.55 (A12O3): 2.1 (Na2O): 3.2 (PI): 280 (H2O). Stir for 0.5 h, then crystallize at 160° C. for 40 h, centrifuge, wash, dry and calcine at 550° C. to obtain a FER molecular sieve.
[0068] The other steps remained unchanged to prepare a 1% Ru-FER-DP-Na catalyst, and the conversion rate was tested using the same steps.
[0069] The specific preparation parameters of each embodiment and comparative example and the conversion rate at different temperatures are shown in Table 1.
[0070] Table 1
[0071]
[0072] It can be seen from Examples 1-5 that the catalyst prepared by the preparation method of Example 1 has a better catalytic effect in the production of hydrogen by decomposing ammonia, and the conversion rate of the catalyst of Example 1 at 500° C. reaches 100%.
[0073] From the comparison of Example 1, Example 6-9, and Example 2, Example 13-16, it can be seen that the increase in the mass fraction of ruthenium in the molecular sieve catalyst can improve the conversion rate of ammonia. For the preparation method of Example 1, when the mass fraction of ruthenium is 1% or more, 500°C can reach a conversion rate of 100%, and for the preparation method of Example 2, when the mass fraction of ruthenium is 2% or more, 500°C can reach a conversion rate of 100%. It can be seen that the ruthenium-loaded molecular sieves of the present invention have good catalytic effects, significantly reduce the operating temperature of the ruthenium-based catalyst, and reduce the cost of hydrogen production by decomposing ammonia.
[0074] It can be seen from Examples 3 and 10-12 that as the mass space velocity increases during the decomposition reaction, the conversion rate decreases. In Example 10, at a mass space velocity of 3000 mL·h -1 ·g -1 The conversion rate at 500°C is 97.394%.
[0075] It can be seen from Example 1 and Comparative Examples 1-4 that when other molecular sieves are used in Comparative Examples 1-4, the catalytic efficiency of the prepared ruthenium-loaded molecular sieve catalyst in hydrogen production by ammonia decomposition is relatively poor, and the conversion rate at 500°C is less than 85%. It can be seen that the sodium ion-rich SOD molecular sieve of the present invention has an excellent catalytic effect after being loaded with ruthenium.
[0076] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a catalyst for hydrogen production by decomposing ammonia, characterized in that: The steps include: S1, mixing aluminum source, silicon source, sodium hydroxide and water to prepare gel, and obtaining a SOD molecular sieve rich in sodium ions after high temperature crystallization; S2, mixing the SOD molecular sieve with a ruthenium salt, subjecting the mixture to high temperature heat treatment and forming to obtain a ruthenium-loaded SOD molecular sieve; Wherein, the mass fraction of ruthenium in the ruthenium-loaded SOD molecular sieve is 0.1%-20%.
2. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 1, characterized in that: In S2, the mixing method is one of coprecipitation, ball milling and impregnation.
3. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 2, characterized in that: The co-precipitation is specifically as follows: mixing the SOD molecular sieve with a ruthenium salt aqueous solution with a mass concentration of 0.5 mol / L-2 mol / L, stirring at a pH of 8.5-9.5, filtering, washing and drying after precipitation.
4. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 2, characterized in that: The impregnation specifically comprises: mixing the SOD molecular sieve, the ruthenium salt and the deionized water and drying them.
5. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 2, characterized in that: When the mixing method is coprecipitation or impregnation, the high temperature heat treatment is calcination at 300-600°C and reduction in a hydrogen atmosphere at 500-600°C; when the mixing method is ball milling, the high temperature heat treatment is reduction in a hydrogen atmosphere at 500-600°C.
6. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 1, characterized in that: In S2, the ruthenium salt is one or more of ruthenium nitrate hexahydrate, ruthenium carbonate, and ruthenium chloride.
7. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 1, characterized in that: In S1, the molar ratio of sodium, aluminum and silicon in the SOD molecular sieve is 7.5:1:(1-4).
8. A catalyst for producing hydrogen by decomposing ammonia prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the catalyst for hydrogen production by decomposing ammonia according to claim 8, characterized in that: The catalyst is loaded in a fixed bed reactor, and ammonia passes through the catalyst bed to undergo a decomposition reaction at 200-600°C.
10. The use of the catalyst for hydrogen production by decomposition of ammonia as claimed in claim 9, characterized in that: The mass space velocity of the decomposition reaction is 600-60000 mL·h -1 ·g -1 .
Citation Information
Patent Citations
A ruthenium-based catalyst for hydrogen production from ammonia decomposition and its preparation method
CN107876796B
On-board vehicle ammonia and hydrogen generation
CN110678630A
Packaging method of Ni@ZSM-5 bifunctional catalyst
CN111250152A
Ru-based catalyst for hydrogen production through ammonia decomposition and preparation method of Ru-based catalyst
CN114570361A
Preparation method of zeolite molecular sieve encapsulated metal catalyst for methane dry reforming
CN116371460A
Cited By
Supported nickel catalyst, preparation method thereof and method for producing hydrogen through ammonia gas decomposition
CN120515488A
Molecular sieve limited range ammonia cracking hydrogen production catalyst and preparation method thereof
CN121360601A